2006
DOI: 10.1158/0008-5472.can-05-4430
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Domains of BRCA1 Critical for the Ubiquitin-Dependent Inhibition of Centrosome Function

Abstract: The breast and ovarian cancer specific tumor suppressor BRCA1, bound to BARD1, has multiple functions aimed at maintaining genomic stability in the cell. We have shown earlier that the BRCA1/BARD1 E3 ubiquitin ligase activity regulates centrosome-dependent microtubule nucleation. In this study, we tested which domains of BRCA1 and BARD1 were required to control the centrosome function. In the present study, (a) we confirmed that the ubiquitination activity of BRCA1 regulates centrosome number and function in H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 39 publications
1
67
0
Order By: Relevance
“…Therefore, when replication forks are stalled in response to exposure to hydroxyurea or radiation, the frequency of supernumerary centrosomes increases in checkpoint-efficient cells because DNA replication is delayed (9,10). However, the disruption of BRCA1 also induces supernumerary centrosomes in the absence or presence of hydroxyurea, although BRCA1-deficient cells continue DNA replication in the presence of DNA damage (11). BRCA1 is directly involved in the maintenance of centrosome duplication through the ubiquitination of g-tubulin, the main component of centrosomes, and the disruption of ubiquitination sites results in an excess number of centrosomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when replication forks are stalled in response to exposure to hydroxyurea or radiation, the frequency of supernumerary centrosomes increases in checkpoint-efficient cells because DNA replication is delayed (9,10). However, the disruption of BRCA1 also induces supernumerary centrosomes in the absence or presence of hydroxyurea, although BRCA1-deficient cells continue DNA replication in the presence of DNA damage (11). BRCA1 is directly involved in the maintenance of centrosome duplication through the ubiquitination of g-tubulin, the main component of centrosomes, and the disruption of ubiquitination sites results in an excess number of centrosomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The control of centrosome number is of interest because breast cancer tumor cells accumulate supernumerary centrosomes, which likely contribute to the aneuploidy that is common in lesions (10,11). Importantly, it has been shown that BRCA1 directly regulates centrosome microtubule nucleation activity (5,12). BRCA1, a 1,863 amino acid phosphoprotein, exhibits E3 ubiquitin ligase activity as a heterodimer with BRCA1-associated RING domain 1 (BARD1; refs.…”
Section: Introductionmentioning
confidence: 99%
“…13,14). The ubiquitin ligase activity is critical for the inhibition of centrosome function because the expression in cells of a point mutant of BRCA1 that can no longer function as a ubiquitin ligase causes the dominant-negative phenotype of centrosome amplification and hyperactive centrosomes (12). Many cancerassociated mutations of the BRCA1 gene directly affect the E3 ubiquitin ligase activity because they alter the structure of the RING domain and inactivate this enzymatic activity (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Cells with mutated lysines on gamma-tubulin, unable to be ubiquitinated, were characterized by centrosome amplification. On the other hand, the same phenotype was observed after inhibition of the enzymatic activity of BRCA1 by transfection of the BRCA1 (I26A) ligase-defective mutant (Sankaran et al, 2006). Additionally, in vitro experiments using Xenopus extracts, purified centrosomes and BRCA1 together with ubiquitination factors confirmed that BRCA1 is involved in the microtubule nucleation.…”
Section: Brca1 In the Regulation Of Centrosome Number And Functionmentioning
confidence: 53%